PENGARUH PEMAHAMAN ETIKA BISNIS ISLAM PEDAGANG MUSLIM TERHADAP PRAKTEK PENIMBANGAN DI KOTA SAMBAS INDONESIAAM PROFIT BISNIS PADA PEDAGANG MUSLIM DI SAMBAS INDONESIA - Sumar’in; Andi Maryam; Mokmin Basri (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
Sharias-based ethics seems to be a trend that can increase profits or as a way to attract customers. As well as the increasing literacy of the community or business actors who are not only looking for profits but also getting blessings from Allah Swt. This study will examine the extent to which Muslim Traders' Islamic Business Ethics Understanding of Weighing Practices. This research was conducted at the Sambas Morning Market. The samples used are permanent traders in Pasar Pagi, who have stalls, and are Muslim. The number of samples to be studied is 30 traders in the Morning Market. This research focuses on Weighing Practices carried out by traders. The analytical tool in this study is to use Linear Regression. Based on the results of the study, it can be concluded that there is a significant influence between the Understanding of Muslim Trader's Islamic Business Ethics on Weighing Practices. Based on the description above, it is interesting to investigate further whether there is an influence between Islamic business ethics and profit.